Microstructural evolution and tensile properties of al–20 wt%Mg2Si–0.2 wt%Ba composite solidified under different cooling rates - Is Prima Nanda; Hamidreza Ghandvar; Andril Arafat (International Journal of Lightweight Materials and Manufacture, 2024)
In recent year, Al–Mg2Si composite becomes a topic to be discussed whether there is a potential to replace common automotive material, Al–Si in applications like piston and brake disk. However, the course with a sharp corner of primary Mg2Si act as the stress concentration promote the initiation of crack to propagate, resulting in low mechanical and tribological performance. Hence, modification of Mg2Si particles in Al–Mg2Si composite is a prime concern. In the current work, the impact of cooling rates on the modification primary Mg2Si crystal shape in 0.2 wt% Ba modified Al–20%Mg2Si composite was evaluated. With mould preheating in different temperatures, the cooling rate was controlled. When the mould temperature is lowered, the cooling rate is increased which causes primary Mg2Si crystal formation with different structures due to Ba atoms adsorption on {100} facets of Mg2Si crystal which can be considered as external factors strengthening. Once the temperature of mould reduced from 600 °C to 400 °C, 200 °C and lastly to 25 °C, the primary Mg2Si morphology changed from octahedral to truncated octahedral, truncated cube and finally to a cube respectively. Tensile results showed that Al–20%Mg2Si-0.2%Ba composite solidified in the mould with temperature of 600 °C, the values of UTS and El% are higher than other composites solidified in other mould temperatures. Furthermore, the tensile fracture surface of Al–20%Mg2Si-0.2%Ba composite solidified in the mould with temperature of 600 °C depicted less decohesion and debonding of the primary Mg2Si particles in the aluminium matrix together with fine dimples on the fracture surface which elucidate the ductile fracture mechanism. The size and structure of the primary Mg2Si in the Al–Mg2Si composite can be regulated by using this practical, affordable approach, leading to the use of this composite in industrial products.